A new sesquineolignan and four new neolignans isolated from the leaves of Piper betle, a traditional medicinal plant in Myanmar. (1st January 2021) - San, Thae Thae; Wang, Yue-Hu; Hu, Dong-Bao; Yang, Jun; Zhang, Dong-Dong; Xia, Meng-Yuan; Yang, Xue-Fei; Yang, Yong-Ping
Graphical abstract: Abstract: One new sesquineolignan, piperneolignan A (1 ), four new neolignans, piperneolignans B–E (2 –5 ), and eight known compounds were isolated from the leaves of Piper betle (Piperaceae) collected from Myanmar. These new structures were determined by analysis of MS and NMR data, and the absolute configuration of piperneolignan A was elucidated by electronic circular dichroism (ECD) calculations. Piperneolignan A (1 ), piperneolignan B (2 ), hydroxychavicol (6 ), p -hydroxycinnamaldehyde (10 ), and diallylcatechol (13 ) possessed anti-inflammatory activity against nitric oxide (NO) production in lipopolysaccharide (LPS)-activated murine macrophage RAW 264.7 cells with IC50 values of 9.87, 45.94, 4.80, 26.40, and 40.45 μM, respectively, compared with the positive control NG-monomethyl-l -arginine (l -NMMA, IC50  = 33.84 μM). The two hydroxy groups in the structure of hydroxychavicol are essential for activity, and dimerization or trimerization of hydroxychavicol decreases activity.